2019
DOI: 10.29273/jmst.2019.3.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Support Surfaces on Activation of Tibialis Anterior, Peroneus Longus, and Gastrocnemius Muscles during Squat Performance

Abstract: Background Previous studies have reported various advantages of general squat for functional activities. However, no study has reported the effect of lower leg muscle activity during squat on ankle stability with different supporting surface conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fourth, muscle activity showed a significant increase in the tibialis anterior, a significant decrease in the medial GCM, and a significant increase in the lateral GCM. Yoon et al (2019) 38) reported increased muscle activities in the peroneus longus and lateral GCM on stable ground and also in the tibialis anterior and medial GCM on unstable ground. Previous studies have shown that ankle control training on unstable ground increased the activity of the peroneus longus and lateral GCM muscles, 38) thereby reducing anterior-posterior shifts in foot pressure.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, muscle activity showed a significant increase in the tibialis anterior, a significant decrease in the medial GCM, and a significant increase in the lateral GCM. Yoon et al (2019) 38) reported increased muscle activities in the peroneus longus and lateral GCM on stable ground and also in the tibialis anterior and medial GCM on unstable ground. Previous studies have shown that ankle control training on unstable ground increased the activity of the peroneus longus and lateral GCM muscles, 38) thereby reducing anterior-posterior shifts in foot pressure.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Yoon et al (2019) 38) reported increased muscle activities in the peroneus longus and lateral GCM on stable ground and also in the tibialis anterior and medial GCM on unstable ground. Previous studies have shown that ankle control training on unstable ground increased the activity of the peroneus longus and lateral GCM muscles, 38) thereby reducing anterior-posterior shifts in foot pressure. 30) The present study showed an increase in muscle activity in the lateral GCM, suggesting that the intervention in this study should be beneficial for ankle stability as well as balance.…”
Section: ⅳ Discussionmentioning
confidence: 99%